Analisis Kurikulum Bahasa Arab dalam Pembelajaran Hadis di Pondok Pesantren Darussunah Ciputat - Hanum Qurrotu Aini; Amalia Qur’ani Masykur; Khoirotunnisa Khoirotunnisa; Maswani Maswani (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
This study aims to analyze the Arabic language curriculum at Darussunnah Islamic Boarding School (Pesantren), Ciputat, with a particular focus on its integration with hadith studies. Arabic is positioned not merely as a subject of study but as a fundamental tool in accessing classical Islamic texts. Employing a descriptive qualitative method, this research involved observation, interviews, and document analysis. The findings reveal that Arabic instruction at Darussunnah is implemented through two main pathways: formal classroom learning (covering grammar, morphology, rhetoric, and TOAFL preparation) and non-formal environmental immersion through activities such as ta?b?q al-lughah, mudz?karah, and scholarly halaqah. Moreover, the assessment system includes both formative and summative components, emphasizing students’ reading, writing, and speaking skills. A culminating task in the form of a takhrij hadith thesis defense requires students to articulate their findings in Arabic. These results indicate that the Arabic curriculum at Darussunnah is designed to be integrative, functional, and contextually relevant, thereby supporting deep engagement with hadith scholarship